IMPROVING MUFRADHAT MASTERY THROUGH ANIMATED VIDEO MEDIA FOR CLASS VIII STUDENTS OF IT AL-FIKRI JUNIOR HIGH SCHOOL MAKASSAR - Fauziah Bachtiar; Aflaha Rahayu; Hasmawati (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research is a descriptive qualitative research that aims to determine the planning, process, and results of mastery of vocabulary through animated video media in class VIII students of IT Junior High School Al-Fikri Makassar. The type of research is classroom action research which was conducted in 2 cycles. The research subjects were 29 students of class VIII of IT Al-Fikri Junior High School Makassar. Data collection techniques using observation and tests. The average test score of students in cycle I was 73% then increased in cycle II 91%. Thus, it can be seen that the results of learning Arabic vocabulary through animated video media can be said to have succeeded in improving mastery of Arabic vocabulary in class VIII students of IT Al-Fikri Junior High School Makassar.